Survival from the Brain's Perspective. - Lowen, Walter (World Futures: The Journal of General Evolution, 2003)
The concern about man's harmful impact on the environment focuses attention on the external environment, i.e., the real world out there, which may not survive in a form to support life. But supporting life of an individual is in the hands of that individual's brain, which is primarily concerned with various needs of the internal environment, also referred to as the self. Confronted with diverse and often competing needs, the brain has evolved a complexity in man, which makes it doubtful that any one collective strategy may be effective in preserving the external environment.